Avaliação de deformidades morfológicas em larvas de Thalassomya (Diptera, Chironomidae, Telmatogetoninae) da costa nordeste brasileira - Costa, Elaine Cristina Ribeiro da (Universidade Federal de São Carlos, 2023)
In August 2019, the beaches of the northeastern coast suffered from an oil spill. This event became the largest oil spill ever recorded in the South Atlantic in terms of extent. Oil slicks were recorded in approximately 1004 locations, distributed across 130 municipalities in the northeastern states, Espírito Santos and Rio de Janeiro. Upon reaching the coastal region of Brazil, the oil contaminated several environments, such as mangroves, beaches, reefs and estuaries present on approximately 3,000 km of the coast that was impacted by this material. Marine ecosystems were directly affected, such as intertidal rocky outcrops, rhodoliths, sandy beaches, estuarine systems, seaweed and coral reefs. Mortality of fish, birds, marine mammals, sea turtles, reptiles was recorded and possibly extended to invertebrates. Among aquatic invertebrates, the Chironomidae family (Diptera) is recognized as a bioindicator of environmental quality, in addition to being widely distributed and abundant, certain peculiarities of chironomids favor their use in assessing environmental impacts, when compared to other organisms. In Chironomidae we can observe different types of deformities resulting from different types of contamination, these deformities are usually observed in the head capsule, where the mouthparts, antennae and epipharyngeal comb are inserted. Within this scenario, the objective of this study was to evaluate the impact on Thalassomya gutae populations through morphological parameters in five populations affected by the crude oil spill. As well as, verify whether the presence of oil can cause morphological anomalies of larvae in different populations. 15% of some degree of deformity was recorded in the populations collected in 2020, 11% of the larvae collected in 2021 showed deformity, and in the populations collected in 2016, only two larvae showed mental malformation. Considering the 2016 data as a reference, we can say that the crude oil spill that occurred at the collection points affected the Chironomidae populations. We believe that the populations are presenting teratogenic anomalies, which arise due to changes in cellular development and their malfunction during the larval life cycle. We conclude that the species T. gutae is a good bioindicator of environmental quality when the larvae are analyzed. Considering the adaptations made in this project to the chin deformity protocol developed by CETESB used for continental environments, it can be applied to coastal environments as well
Assessment of morphological deformities in Thalassomya larvae (Diptera, Chironomidae, Telmatogetoninae) from the brazilian northeast coast
Keywords: Derramamento de óleo; HPAs; Bioindicador; CIENCIAS BIOLOGICAS::ZOOLOGIA